English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

integral of [x^5.(x^3 + 1)^(1/3)].dx

2007-01-28 11:06:07 · 3 answers · asked by ♥ Lady in Pink ♥ 2 in Science & Mathematics Mathematics

3 answers

Integ [x^5.(x^3 + 1)^(1/3)] dx

Well your choices are Substitutions and/or Integration by Parts.

(x^2 + 1) or ^(1/2) would suggest a trigonometric/hyperbolic substitution, but (x^3 + 1)^(1/3) doesn't.

(x^3 + 1)^(1/3) is going to be nasty,
so try substitution w=x^3 + 1 , dw=3x^2dx
Noting x^5 = 1/3 * x^3 * 3x^2 ...

Then Integ [x^5.(x^3 + 1)^(1/3)] dx
= 1/3 Integ [x^3.(x^3 + 1)^(1/3) *3x^2 dx]
= 1/3 Integ [(w-1) (w)^(1/3) *dw]
= 1/3 Integ [w^(4/3) - w^(1/3)] dw
= 1/3 (3/7 w^(7/3) - 3/4 w^(4/3)) + C
= w^(4/3) * (1/7 w - 1/4) + C

These things are like an open-ended rope, you can spin yourself into trouble.
The question I always ask myself to check is: did my approach reduce the complexity and/or the order of the expression, or else translate it to some known standard form for which an identity exists? If not, then the step was no good.

In this case you really want to eliminate the (x^3 + 1)^(1/3) term.

2007-01-28 11:15:39 · answer #1 · answered by smci 7 · 0 3

integral of [x^5.(x^3 + 1)^(1/3)].dx = I (Say)
Put y = x^3, then dy =3x^2 dx. Then the above integral becomes:
I = integral of [ (1/3) y (y+1)^(1/3)] dy.
=(1/3) integral of [y(y+1)^(1/3)]dy
=(1/3) integral of [(y+1 -1)(y+1)^(1/3)] dy
=(1/3) integral of [(y+1)^(4/3) -(y+1)^(1/3)] dy
= (1/3)[ (3/7) (y+1)^(7/3) - (3/4) (y+1)^(4/3)] + C(constant)
= (1/28)(y+1)^(4/3) [4y+4 - 7] +C
=(1/28) (4y -3) (y+1)^(4/3) + C. OR
I = (1/28) (4x^3 -3) (x^3 +1)^(4/3) + C., putting back y = x^3.

Verification:
Derivative of this
= (1/28)[(4x^3 - 3) (4/3)(x^3 +1)^(1/3) .3x^2 + 12x^2(x^3+1)^(4/3)]
= (1/7)x^2 (x^3 +1) ^(1/3) [4x^3 - 3 + 3(x^3 +1)]
= x^5 (x^3 +1)^(1/3) OOKKKK.

2007-01-28 20:11:28 · answer #2 · answered by Anonymous · 0 0

Integrate {(x^5)*(x³ + 1)^(1/3)} with respect to x.

∫{(x^5)*(x³ + 1)^(1/3)}
= (1/3)∫{(3x²)(x³)(x³ + 1)^(1/3)}dx

Let
u = x³ + 1
du = 3x² dx
u - 1 = x³

= (1/3)∫{(u - 1)[u^(1/3)]}du = (1/3)∫{u^(4/3) - u^(1/3)}du
= (1/3){(3/7)u^(7/3) - (3/4)u^(4/3) + C
= (1/7)u^(7/3) - (1/4)u^(4/3) + C
= {4u^(7/3) - 7u^(4/3)} / 28 + C
= {4(x³ + 1)^(7/3) - 7(x³ + 1)^(4/3)} / 28 + C
= (x³ + 1)^(4/3){4(x³ + 1) - 7} / 28 + C
= (x³ + 1)^(4/3){4x³ - 3} / 28 + C

2007-01-28 19:53:14 · answer #3 · answered by Northstar 7 · 0 0

fedest.com, questions and answers